Addressing Spacer Channel Resistances in MCDI Using Porous and Pliable Ionic Conductors. Issue 3 (18th March 2021) - Palakkal, Varada Menon; Jordan, Matthew L.; Bhattacharya, Deepra; Lin, Yupo J.; Arges, Christopher G.
Abstract : Membrane capacitive deionization (MCDI) is a unique electrochemical separations platform that allows for energy recovery during electrode regeneration. Similar to other electrochemical separation technologies producing deionized water (e.g. electrodialysis), ohmic resistances in the spacer channel significantly hampers the performance and energy efficiency of the process. This work devised a series of ionomer coated nylon mesh nets to address spacer channel resistances in MCDI. Under constant current operation, the ionomer coated nylon meshes displayed a 300 mV lower cell voltage rise during deionization while sustaining the same deionization rate. Furthermore, energy recovery was improved by 1.4x to 5.5x depending on the saline feed concentration. The lower cell voltage rise during deionization combined with the greater energy recovery with ionomer coated meshes resulted in energy normalized adsorbed salt (ENAS) values that were 2x to 3x greater. Addressing the spacer channel resistances in MCDI allowed for 8% to 19% increase in current density without the cell voltage exceeding 1.6 V—the upper bound set for mitigating parasitic reactions. Operating at higher current density leads to smaller MCDI units for a given deionization requirement and has implications for reducing the capital costs of the MCDI unit.